THE IMPACTS AND INFLUENCES OF DIGITAL SCREEN USE ON CHILD NEURODEVELOPMENT (Interdisciplinary Studies Journal, 2025)
The research investigates the impacts of excessive digital screen use on children's neurodevelopment, focusing on cognitive, emotional, social, and physical effects in children and adolescents. The increasing exposure to electronic devices has raised concerns about their effects on brain development, particularly in areas such as language, cognition, memory, and social interactions. Studies suggest that early and prolonged exposure can lead to developmental delays, as well as contribute to health problems such as sleep difficulties, obesity, and emotional disorders. The research was conducted with a sample of parents and guardians through questionnaires addressing screen time, the most used devices, and perceptions regarding the impacts on children's development. The results indicate that most children exceed the recommended screen time, with 33.3% using devices for two to four hours daily, and 26.7% using them for more than four hours. The research also revealed that, although screen use is often associated with educational benefits, the risks related to exposure to inappropriate content and sedentary behavior are significant. Additionally, it was found that most parents set screen time limits, although there is variation in the strictness of these rules. This study highlights the need for educational strategies and public policies to promote a balanced and healthy use of technology, with the active participation of parents, educators, and healthcare professionals, aiming to mitigate the negative effects of excessive screen exposure on child development.
Keywords: Technological education; Digital screens; Neurodevelopment; Childhood; Cognitive impacts; Mental health